2019
DOI: 10.1002/ange.201813048
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Azaproline Confers pH Responsiveness and Functionalizability on Collagen Triple Helices

Abstract: Proline derivatives bearing substituents at Cγ are valuable tools for biological and materials investigations. However, the stereochemistry at Cγ can produce undesired steric or stereoelectronic interactions. Here, we introduce γ‐azaproline (γ‐azPro), which lacks a stereogenic center at Cγ, as a pH‐responsive and functionalizable proline analogue that can adapt to its environment. Conformational analyses by NMR spectroscopy and DFT calculations revealed that the imidazolidine ring of γ‐azPro is flexible. Incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…1,18,19 Therefore, we have started studying the water/collagen interaction before and after Pro hydroxylation. Finally, the approach presented here can be used side by side with experimental collagen investigations, 22,[58][59][60][61][62][63][64] as complementary, reliable, accurate and parameter-free methodology.…”
Section: Discussionmentioning
confidence: 99%
“…1,18,19 Therefore, we have started studying the water/collagen interaction before and after Pro hydroxylation. Finally, the approach presented here can be used side by side with experimental collagen investigations, 22,[58][59][60][61][62][63][64] as complementary, reliable, accurate and parameter-free methodology.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, a variety of 4 R ‐ and 4 S ‐proline derivatives have been incorporated into either the X position or the Y position within X–Y–Gly triads to explore the consequences of their pucker preference on collagen conformation (Bretscher et al, 2001; Doi et al, 2003; Hodges & Raines, 2003; Inouye et al, 1982; Kotch et al, 2008; Shoulders, Kotch, et al, 2010). In additional to applying the 4 R ‐ and 4 S ‐proline derivatives to adjust the needs of the triple helical environment, γ‐azaproline, the nitrogen analog of Thp, was also used to probe the pH‐responsiveness on collagen triple helices (Aronoff et al, 2019, 2020). Surprisingly, no studies have been reported to use the proline analog, Thp, as a substituent in CMPs to examine its impacts on a collagen triple helix.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, three collagen single strands form a right‐handed triple helix that is stabilized through interstrand H‐bonds and intrastrand n→π* interactions between neighboring amides [15,23] . CMPs bearing γ‐aminoproline (Amp), Azp, or aminooxyproline (Aop) allowed for derivatization of collagen triple helices via amidation, copper(I)‐catalyzed azide alkyne cycloaddition (CuAAC), and oxime ligation, both in vitro and in vivo [21,24–29] . We envisioned that the isonitrile functional group would complement these extant technologies and allow for dual labelling.…”
Section: Introductionmentioning
confidence: 99%